EVALUASI LAYANAN BROADBAND CAMPUS DENGAN MENGGUNAKAN FRAMEWORK COBIT 4.1 - Prabowo, Fajar Tri; Wirastuti, NMAE Dewi; Kumara, I Nyoman Satya (Jurnal Teknologi Elektro; Vol 16 No 2 (2017): (May - Agustus) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2017.v16i02p06, 2017)
Abstract - Broadband campus is a high speed internet service with high transfer rate that implemented within the campus area. The sole purpose of this service is to optimize the internet network in certain area that is still lack of a high speed internet connection. This paper will ellaborate more on the evaluation of certain ongoing broadband campus service at Mahasaraswati University in Denpasar by using COBIT 4.1 Framework. This evaluation is intended to enhance the user effectiveness through existing services. This evaluation was conducted through certain mini-survey by using the broadband campus IT service by examining the university students satisfaction through series of interviews and questionnaires. The conclusion that was inferred through the surveys is that the broadband services within the university gain a subsequently low existing maturity level with 1.9 mark in the COBIT Framework scale. One of the major reason of why the service acquire low satisfaction level within the university is due the students in Mahasaraswati University did not manage to optimize the broadband campus service in the first place
Keywords: Broadband, COBIT 4.1, Framework, Awareness